1975
DOI: 10.1159/000155698
|View full text |Cite
|
Sign up to set email alerts
|

Added Heterochromatin Segments in Chromosomes of Squirrel Monkeys (<i>Saimiri sciuveu</i><i>s</i>)

Abstract: Variant structural homozygosity, observed previously only in plants and insects, is reported herein for the first time in mammalian chromosomes. The addition of a heterochromatic chromosome segment to either one or both homologues is described in autosomes B5 and B12 of the squirrel monkey, Saimiri sciureus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 14 publications
(18 reference statements)
1
10
0
Order By: Relevance
“…Among Platyrrhini species, quantitative and qualitative modifications of heterochromatin can be illustrated with genera like Ateles (Nieves et al 2005a) and Saimiri (Ma and Jones 1975). A particular case is Cebus, which presents heteromorphisms of heterochromatic blocks throughout populations (Dutrillaux et al 1978;Seuánez et al 1986;Mudry de Pargament and Labal de Vinuesa 1988;Ponsà et al 1995;Martinez et al 2004;Nieves et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Among Platyrrhini species, quantitative and qualitative modifications of heterochromatin can be illustrated with genera like Ateles (Nieves et al 2005a) and Saimiri (Ma and Jones 1975). A particular case is Cebus, which presents heteromorphisms of heterochromatic blocks throughout populations (Dutrillaux et al 1978;Seuánez et al 1986;Mudry de Pargament and Labal de Vinuesa 1988;Ponsà et al 1995;Martinez et al 2004;Nieves et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The C positive heterochromatic bands are usually G positive. So far, the presence of different amounts of heterochromatin has been described in homo zygosis and/or heterozygosis for pairs A5, B5 and B12 [Ma and Jones, 1975;Lau and Arrighi, 1976].…”
Section: Discussionmentioning
confidence: 99%
“…C-banding studies carried out by Ma and Jones [1975] and by Lau et al [1977] have revealed a second type of intraspecific chromosomal polymorphism due to the presence of different amounts of constitutive heterochromatin in the short arms of pairs B5 and B12. Ma et al [1974] and Lau and Arrighi [1976] have also studied one animal each with a heterozygous pair made of one nonacrocentric and one acrocentric chromosomes.…”
mentioning
confidence: 99%
“…The mitotic chromosomes of primates, among them the genus Saimiri, have been widely investigated. The diploid number for all Saimiri species is 44 chromosomes (2N 5 44, XX/XY) with differences in their karyotypes due to pericentric inversions [Ma & Jones, 1975]. The acrocentrics/non-acrocentrics ratio allows a clear identification of full species and hybrids both in captivity and the wild [Moore et al, 1990].…”
Section: Introductionmentioning
confidence: 99%